A whiff of murder [large type] - Sanders, Angela M. ([Sixth sense mysteries] ;, 2026)
"Some people read auras--a light or color that surrounds others, revealing their character or emotions. Lise Bloom reads ribbons--of fragrance, that is. Whether she's around old friends or new, fragrance often unfurls from them--an ability called "clairalience." Hoping to gain insight into her gift, Lise works at the Lucky Lotus, a New Age shop. Unfortunately, the oils the owner, Dyann, concocts, nauseate Lise and impede her sense of scent. Worse, the shop feels more like wealthy Dyann's hobby than a spiritual place, thanks to her toxic love-torment relationship with her ex-husband, Richard. Dyann is so pleased with her latest vengeful scheme that she shares it with Lise and gleefully remarks that when Richard finds out, he'll kill her. For Lise, it's the last straw. Persuaded to quit by her caring, colorful crew of housemates, Lise emails Dyann a resignation letter. But when she goes to the store the next morning, she detects a fetid odor she doesn't recognize--and discovers a spilled bottle of Mayan ceremonial liqueur . . . beside Dyann's dead body. In her rush to call the police, Lise doesn't notice that Dyann's half-completed reply to Lise's resignation email is on the monitor of her desktop computer--making her the prime suspect. Now, she'll have to follow her nose to uncoil a venomous truth. It just may lead her life in an entirely new direction--unless a killer cuts it short . . ."--